2021
DOI: 10.1021/acsmedchemlett.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent 3-Br-isoxazoline-Based Antimalarial and Antileishmanial Compounds

Abstract: Starting from the structure of previously reported 3-Br-isoxazoline-based covalent inhibitors of P. falciparum glyceraldehyde 3-phosphate dehydrogenase, and with the intent to improve their metabolic stability and antimalarial activity, we designed and synthesized a series of simplified analogues that are characterized by the insertion of the oxadiazole ring as a bioisosteric replacement for the metabolically labile ester/amide function. We then further replaced the oxadiazole ring with a series of five-member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The N -acylated derivatives were submitted to a cyclization reaction using hexachloroethane, N,N -diisopropylethylamine, and triphenylphosphine in acetonitrile at room temperature to afford 2,5-disubstituted 1,3,4-oxadiazoles 62 – 71 . These intermediates are characterized by the presence of a vinyl substituent in the 2 position, which represents a good dipolarophile for the subsequent 1,3-dipolar reaction that was used to build the 3-bromo-4,5-dihydroisoxazole (BDHI) nucleus . Indeed, alkenes 62 – 71 reacted with bromonitrile oxide, generated in situ from its stable precursor dibromoformaldoxime (DBF) in the presence of solid NaHCO 3 as a heterogeneous base and ethyl acetate as an organic solvent, to give final compounds 20 – 29 in good to quantitative yields (57%-quantitative).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The N -acylated derivatives were submitted to a cyclization reaction using hexachloroethane, N,N -diisopropylethylamine, and triphenylphosphine in acetonitrile at room temperature to afford 2,5-disubstituted 1,3,4-oxadiazoles 62 – 71 . These intermediates are characterized by the presence of a vinyl substituent in the 2 position, which represents a good dipolarophile for the subsequent 1,3-dipolar reaction that was used to build the 3-bromo-4,5-dihydroisoxazole (BDHI) nucleus . Indeed, alkenes 62 – 71 reacted with bromonitrile oxide, generated in situ from its stable precursor dibromoformaldoxime (DBF) in the presence of solid NaHCO 3 as a heterogeneous base and ethyl acetate as an organic solvent, to give final compounds 20 – 29 in good to quantitative yields (57%-quantitative).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, two synthons 74 and 76 were separately prepared and then coupled using standard conditions (EDC•HCl, HOBT, and TEA), leading to intermediate 77. Finally, 77 was cyclized by treatment with hexacloroethane, N,N-diisopropylethylamine, and triphenylphosphine in acetonitrile to yield the desired probe (30) in a 74% yield (Scheme 2). Carboxylic acid 74 was obtained in two steps and 80% yield from the commercially available ethyl acrylate, which was submitted to 1,3-dipolar cycloaddition with DBF, followed by ester hydrolysis with a 1 M aqueous solution of NaOH and dioxane.…”
Section: T Brucei Phenotypic Screening Of the In-housementioning
confidence: 99%
See 1 more Smart Citation
“…3-Halo-4,5-dihydroisoxazoles (3-halo­isooxazolines) such as the natural product acivicin ( 123 ) and its more active synthetic 3-bromo-4,5-dihydro­isoxazole (BDHI) derivative 124 (Figure A) are well known for their ability to covalently inhibit cysteine-dependent enzymes like human trans­glutaminase 2 and for their activity on parasitic enzymes. Such compounds have been subject to early reactivity/​promiscuity analyses which showed that the reaction proceeds through an addition–elimination mechanism, displacing the halogen at the electrophilic 3-position, which has been hypothesized to be favored in protease-like enzymes by stabilization of the tetrahedral intermediate via the oxyanion hole . With respect to human target proteins, Pinto et al recently showed by MS and X-ray crystallography (PDB code: 6FFM) that the BDHI 125 (Figure A) covalently binds to Cys151 of the KEAP1 protein, allowing the modulation of the antioxidant system NRF2/HO-1.…”
Section: Targeting the Cysteine Side Chainmentioning
confidence: 99%
“…Successful efforts to obtain the compounds containing medium rings, in most cases with heteroatoms, have been recently reported, illustrating the arising interest in such structures and the need for synthetic methods for them [15][16][17]. Isoxazoles and isoxazolines reveal a broad range of biological activities, including antitumor, antibacterial, antimalarial, antisclerotic, antidiabetic, and others (Figure 1), and a number of examples exist of how the insertion of an isoxazoline moiety increases the potency of the bioactive compounds [18][19][20][21][22][23]. The most general approach to isoxazoline derivatives is 1,3-dipolar cycloaddition, though other methods, taking advantage of metal-mediated and radical processes, are constantly gaining more significance [24,25].…”
Section: Introductionmentioning
confidence: 99%